Bagaimana Iklim Etis Dan Gaya Kepemimpinan Berpengaruh Terhadap Efektifitas Pemimpin? - Iqbal robbie; Ardik Praharjo (Islamic University of Kalimantan MAB Banjarmasin, 2020)
This study aims to determine the relationship between ethical climate and leadership effectiveness in companies with ethical leadership variables as intervening variables. Ethical leadership is based on the diversity of situations and conditions in the company and personal values within the leader so as to allow conflict or good synergy between employees. The population of this study were all permanent employees under the medical services division, especially the nursing field, totaling 133 employees at the Muhammadiyah University Hospital, Malang. The research variables will be elaborated through a questionnaire which will be distributed to respondents based on the total amount, because all pupulation is used as research objects. Data collected will be processed using the analysis